Influencing beach littering behaviors through infrastructure design: An in situ experimentation case study. (July 2020) - Portman, Michelle E.; Behar, David
Abstract: Marine litter is one of the most pressing problems of our time and a major threat to ocean health; much of it comes from land-based sources, including from beachgoer activities. This study investigates how product design could influence littering behaviors of beachgoers when applied to beach trash cans (TCs). Over the course of six weeks three differently designed TCs were placed on a Mediterranean Sea tourist beach in Israel while observers tracked the behavior of 536 nearby groups ("entities") of beachgoers. Researchers analyzed: a) entities' locational choices; b) materials discarded in the TCs; and c) littering behaviors around the TCs. Based on the data collected, a "motivating" TC design performed best, encouraging the highest level of beachgoer interaction. Further research is needed in more and varied beach contexts, but this type of initial interdisciplinary research suggests how the design discipline could contribute to preventing marine litter from land-based sources. Highlights: Marine litter effects can be addressed by better design of beach infrastructure. Two experimental beach trash can (TCs) designs (prototypes) were developed. Interactions with the two prototype trash cans were compared to a control. Behaviors of beachgoers interactions with the 3 different TCs were compared. The greatest beachgoer interaction occurred with the "motivating" TC.